Trends in prevalence of hypertension and high-normal blood pressure among US adults, 1999–2018 - Ting Wang; Huizhen Liu; Xiaoqin Zhou; Changxi Wang (Scientific Reports)
Abstract Hypertension and high-normal blood pressure (BP) increase the risk for cardiovascular diseases. Examining trends in hypertension and high-normal BP among US adults is crucial. Participants aged 20 years or older from the 1999–2018 National Health and Nutrition Examination Surveys, were included. Trend analyses were performed to assess temporal changes in prevalence of hypertension and high-normal BP among US adults. Among the 48,580 participants included in this analysis, the mean (SD) age was 47.2 years (18 years) and 50.9% were women. Age-adjusted prevalence of hypertension was stable from 1999 to 2000 (29.5% [95% CI 26.6–32.3%]) through 2017–2018 (31.9%, [95% CI 29.0–34.7%]) (P = 0.265 for linear trend). Age-adjusted prevalence of high-normal BP decreased from 10.9% (95% CI 9.4–12.5%) in 1999–2000 to 8.0% (95% CI 7.1–9.0%) in 2007–2008, then increased to 9.8% (95% CI 8.3–11.3%) in 2017–2018 (P = 0.002 for nonlinear trend). Compared with men, hypertension and high-normal BP was less likely among women (multivariable-adjusted prevalence ratio, 0.90 [95% CI 0.84–0.97]; 0.68 [95% CI 0.52–0.88], respectively). Compared with non-Hispanic Black, high-normal BP was less likely among Mexican American, non-Hispanic White, and other race (multivariable-adjusted prevalence ratio, 0.59 [95% CI 0.44–0.79]; 0.53 [95% CI 0.41–0.69]; 0.56 [95% CI 0.74 − 0.71], respectively). The same held for hypertension.